IMMUNOGENICITY ASSESSMENT FOR DETERMINATION OF THE MOST POTENTIAL ISOLATES OF KOIHERPES VIRUS - Lila Gardenia; Isti Koesharyani; Tatik Mufidah (Indonesian Aquaculture Journal, 2015)
Common carp and koi (Cyprinus carpio) are the main consumption fish commodity and ornamental fish in Indonesia. Diseases due to koiherpes virus (KHV) infection had caused a huge loss in both common carp and koi culture industries world-wide. This study was generated to select the most potential candidate from out of three koiherpes virus isolates based on their serological performances for vaccine development to control Koiherpes virus disease in koi. Virus collection, isolation, and propagation in cell culture have been conducted from common and koi samples originated from Banjarmasin, South Kalimantan; Takalar, South Sulawesi; Cirata Lake-Cianjur, West Java; Depok, West Java; Ciseeng, Bogor, West Java; and Purwokerto, Central Java. Determination of the causative agent of the disease was done by PCR (Polymerase Chain Reaction) assay and inoculation of filtrate homogenates from infected fish into cell culture. There are three koiherpes virus isolates (BJMN-1, BJMN-2, and SKBM) which are being successfully isolated, cultured and propagated in Koi Fin (KF-1) cell line. Calculation of tissue culture infection dose from each isolates were 104.55 TCID50/mL, 104.72 TCID50/mL, and 103.28 TCID50/mL. Immunoassay of the three isolates was conducted by Indirect-ELISA method. Polyclonal antibody was made by injecting each isolate to the experiment animals (rat/Rattus norwegicus strain Sprague Dawley). It was shown that all of three isolates have high level of immunogenicity, as seen from the absorbance values at 490 nm wavelength. BJMN-1 isolates have a higher potential for it’s ability to cross-react with the other isolates and provided the highest absorbance values. In future, all isolates can be used as KHV vaccine candidates to prevent KHV infection.